2023
DOI: 10.1007/s12553-023-00776-w
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health professionals’ experiences with telehealth services: usage, perceived usefulness and ease of use

Sari Nissinen,
Sanna Pesonen,
Pauliina Toivio
et al.

Abstract: Background In occupational health care, telehealth services implementation requires the professionals to change their way of working because they have had to incorporate the telehealth services into their daily routines. Understanding how occupational health professionals relate to and experience telehealth services may aid in its implementation. However, an overview of telehealth services’ use in occupational health care is lacking. The aim of this study was to provide insight into the telehealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Even though digital tools and technology have become more common e.g., in work ability management and occupational co-operation [16,23], our results showed that digital OH services were not yet widely used nor always even available among the employer customers. This came up especially among the subgroup of the entrepreneurs since, depending on the single studied variable, tenth to fifth of the respondents stated that digital tools or digital technology was not available to use.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Even though digital tools and technology have become more common e.g., in work ability management and occupational co-operation [16,23], our results showed that digital OH services were not yet widely used nor always even available among the employer customers. This came up especially among the subgroup of the entrepreneurs since, depending on the single studied variable, tenth to fifth of the respondents stated that digital tools or digital technology was not available to use.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, the study evaluated the employer customers' experiences of, and the factors associated with, the usefulness and ease of use of digital OH services. Focusing on the HR professionals and entrepreneurs give much needed information about the employer customers' experiences of utilizing digital technologies [11,13,14,16,17]. According to our knowledge, we were the first to conduct a study on digital service experiences of employer customers in OH services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to assess whether this change has influenced the professionals' responses. On the other hand, it is also known that the number of remote services has also increased in occupational physiotherapists' service offering, 37 and this trend may have an impact on occupational physiotherapists' views on flexible service provision.…”
Section: Dovepressmentioning
confidence: 99%